SEMANTIC AND STRUCTURAL ANALYSIS OF PHRASEOLOGICAL UNITS WITH THE COMPONENTS OF ANIMALS - Abdumominova Mohinur Faxriddinnovna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article investigates the semantic and structural dimensions of phraseological units placing much emphasis on those containing animal components specially. Analyzing both their internal structure and conveyed meaning provides much insights into how language decodes cultural knowledge, metaphor and idiomatic expression.